2000
DOI: 10.1016/s0167-4889(00)00098-7
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-dependent translocation of S100A11 requires tubulin filaments

Abstract: Protein translocation between different subcellular compartments might play a significant role in various signal transduction pathways. The S100 family is comprised of the multifunctional, small, acidic proteins, some of which translocate in the form of vesicle-like structures upon increase in intracellular Ca(2+) levels. Previously, cells were fixed before and after calcium activation in order to examine the possible relocation of S100 proteins. In this study, we were able to track the real-time translocation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 41 publications
2
22
1
Order By: Relevance
“…2). Such a model is consistent with recent studies demonstrating Ca 2ϩ -dependent changes in the subcellular distribution of S100A2, S100A4, and S100A6 (Davey et al, 2000;Mandinova, et al, 1998;Mueller et al, 1999). There is no question that binding sites on both S100 proteins and individual target proteins will play a critical role in mediating S100-target protein interactions.…”
Section: Introductionsupporting
confidence: 89%
“…2). Such a model is consistent with recent studies demonstrating Ca 2ϩ -dependent changes in the subcellular distribution of S100A2, S100A4, and S100A6 (Davey et al, 2000;Mandinova, et al, 1998;Mueller et al, 1999). There is no question that binding sites on both S100 proteins and individual target proteins will play a critical role in mediating S100-target protein interactions.…”
Section: Introductionsupporting
confidence: 89%
“…Accordingly, S100A14 exhibited different patterns of subcellular distribution, typified by plasma membrane localization in breast cancer tissues but cytosolic expression in nontumor breast epithelial cells (35). Previous studies showed that some members of the S100 family of proteins exhibit calcium-dependent translocation (36,37), and the translocation of S100A14 is regulated in a calcium-dependent manner through interaction with nucleobindin, which has strong association with Ga proteins (38). We also found that calcium treatment induced S100A14 expression in cell nuclei in esophageal cancer cell lines, further suggesting that calcium plays a role in the induction and translocation of S100A14.…”
Section: Discussionmentioning
confidence: 99%
“…Several S100 proteins have been shown to translocate to cytoskeletal elements upon elevation of cytosolic calcium, suggesting that some S100 members have a role in the regulation of cell shape changes, locomotion, and the three-dimensional organization of the cytoskeleton. 20,[33][34][35][36] Preceding studies from our group demonstrated that S100A8/S100A9 complexes promote the formation of MTs in an MT-associated protein-like fashion. It was shown that S100A8/S100A9 bind to tubulin filaments in a calcium-dependent manner, and functional assays demonstrated a role of native S100A8/S100A9 in polymerization and bundling of MTs.…”
Section: Discussionmentioning
confidence: 99%